Teacher's ICT skills and readiness of integrating augmented reality in education - Azrie, Salleh; Eh Phon, Danakorn Nincarean; Ferda, Ernawan; Ismail, Ahmad Yusuf; Adi, Prajanto Wahyu (Institute of Electrical and Electronics Engineers Inc., 2021)
In recent years, the ministry of education has adopted policies aimed at enhancing the consistency and efficacy of the teaching and learning process. In the midst of the Covid-19 pandemic, the implementation of different alternatives to the current teaching and learning mechanism is extremely crucial. With the migration of the current education online, AR is viewed to be a suitable and relevant alternative to be implemented. However, study on teacher readiness to adopt AR in education is still absent. Therefore, there is a need to investigate teacher's ICT skills and their readiness in deploying AR in teaching and learning. This research uses quantitative study and survey as the research methodology with 96 teachers involved as a participant. The data analysis is performed using descriptive analysis with the help of SPSS software. The findings showed that teachers in this research show a minimum to moderate level of expertise skilled in handling different ICT aspects. In addition, the research has also shown that teachers in this study show less familiarity with AR technology. The significance of this study is able to provide a set of empirical results that is beneficial for further education planning by the government.